ANALYZING JUNIOR HIGHSCHOOL STUDENTS’ MOTIVATION IN LEARNING ENGLISH IN NEW NORMAL - Alfianti Tapala, Alma; Suriaman, Aminah; Mashuri, Mashuri (e-Journal of ELTS (English Language Teaching Society), 2023)
The purpose of this research is to design a qualitative research method. In collecting data 30 students and five students were randomly. The research design used questionnaires and interviews. The results of data analysis show that the motivation to learn English in the new normal is high, making them want to go back to school; compared to online learning, students are easier to understand and can achieve learning achievement by returning to school. Based on the statement above, the researcher concludes that it can help students with their willingness to learn again in school in the new normal